Sustainability Reporting, Ukuran Perusahaan, Profitabilitas terhadap Harga Saham dengan Nilai Perusahaan sebagai Variabel Mediasi - Rani Eka Pratiwi; Usep Siswadi; Imas Fatimah (Politeknik Ganesha Medan, 2026)
This study aims to examine the effects of sustainability reporting, firm size, and profitability on stock prices, with firm value serving as a mediating variable. A causal associative quantitative approach was employed using secondary data obtained from annual financial statements and sustainability reports. The sample was selected through purposive sampling, resulting in 50 observations from 10 energy sector companies. Data were analyzed using panel data regression and path analysis with EViews software. The findings indicate that sustainability reporting has a significant positive direct effect on stock prices, supporting signaling theory, which suggests that the disclosure of non-financial information is positively perceived by the market. Profitability has a significant positive effect on firm value but does not directly influence stock prices, reflecting a shift in investor preferences within the energy sector. Meanwhile, firm size has no significant effect on either firm value or stock prices, indicating that asset scale is no longer a primary indicator of market valuation. The mediation analysis further reveals that firm value, measured by Tobin’s Q, mediates only the relationship between profitability and stock prices. These findings imply that energy companies should enhance the quality of their sustainability disclosures as a strategic instrument to improve market value and strengthen investment attractiveness